Intrafamilial Variability of Dermal Ridge Patterns in Subdigital Areas of Feet - Buchwald, Wiesław (Anthropological Review, 1994)
The study is based upon investigations of 700 pairs of parents and their 1808 children (854 sons and 954 daughters) from northern Poland. The children were divided according to the combination of subdigital area ridge patterns of their parents’ feet, and the frequency of occurrence of different ridge patterns was calculated in each group (Tables 2-11). Homolateral similarities to one or both parents were indicated by bold print, heterolateral similarities were printed in italics, while lack of similarities was signalized by normal print. Interdependencies between the analysed dermatoglyphic traits of parents’ and children’s feet were studied by x 2 test and cp indices (Table 12). The percentage of homolateral (Z) and heterolateral (Zh) similarity as well as of dissimilar pattern types (X) were calculated for the five subdigital areas of children’s feet, in comparison with their parents’ feet (Table 13).The results of x 2 test, <p indices and pattern similarity percentages indicate that there exists a statistically significant relationship between parents and children as regards the ridge pattern of subdigital areas of their feet.